2016
DOI: 10.3390/ijms17122067
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a Putative Cytochrome P450 Alkane Hydroxylase (CYP153D17) from Sphingomonas sp. PAMC 26605 and Its Conformational Substrate Binding

Abstract: Enzymatic alkane hydroxylation reactions are useful for producing pharmaceutical and agricultural chemical intermediates from hydrocarbons. Several cytochrome P450 enzymes catalyze the regio- and stereo-specific hydroxylation of alkanes. We evaluated the substrate binding of a putative CYP alkane hydroxylase (CYP153D17) from the bacterium Sphingomonas sp. PAMC 26605. Substrate affinities to C10–C12 n-alkanes and C10–C14 fatty acids with Kd values varied from 0.42 to 0.59 μM. A longer alkane (C12) bound more st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…The identification of octadec‐9‐enoic acid (oleic acid) is consistent with a study reporting the same fatty acid as product of naphthalene metabolism in Nocardiopsis alba RD3. In this bacterium, acids like acetic acid and fumaric acid were also identified [42]. According to this study, different acids like lactic acid and 2‐(aminooxy) propionic acid were also detected as metabolic intermediates in present study bacteria.…”
Section: Discussionsupporting
confidence: 55%
“…The identification of octadec‐9‐enoic acid (oleic acid) is consistent with a study reporting the same fatty acid as product of naphthalene metabolism in Nocardiopsis alba RD3. In this bacterium, acids like acetic acid and fumaric acid were also identified [42]. According to this study, different acids like lactic acid and 2‐(aminooxy) propionic acid were also detected as metabolic intermediates in present study bacteria.…”
Section: Discussionsupporting
confidence: 55%
“…Biochemical and structural studies have investigated and revealed that, although the primary protein structure for bacterial CYPs is not conserved, the secondary and tertiary structures of CYPs are similar to each other [ 12 ]. Sequence alignment studies have shown that the substrate recognition sites (SRSs) composed of five loops are neither conserved nor structurally rigid with various amino acid sequences [ 13 , 14 , 15 , 16 ]. The substrate selectivity or preference among diverse substrates of CYPs is thought to be overcome with highly flexible loops and divergent sequences around SRSs.…”
Section: Introductionmentioning
confidence: 99%